2018
DOI: 10.1167/iovs.17-23327
|View full text |Cite
|
Sign up to set email alerts
|

Hemin Promotes Corneal Allograft Survival Through the Suppression of Macrophage Recruitment and Activation

Abstract: Our results are the first to demonstrate that hemin, a Food and Drug Administration-approved drug, promotes corneal allograft survival. These findings indicate that hemin might be a potential alternative treatment for CGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…[20][21][22] Recent studies indicated that corneal macrophages are critical for corneal wound repair and inflammation. [23][24][25] However, the roles of the corneal macrophages of LCD patients in elimination of the amyloid TGFBIp remain unknown.…”
mentioning
confidence: 99%
“…[20][21][22] Recent studies indicated that corneal macrophages are critical for corneal wound repair and inflammation. [23][24][25] However, the roles of the corneal macrophages of LCD patients in elimination of the amyloid TGFBIp remain unknown.…”
mentioning
confidence: 99%
“…Our previous study proved that IL-27Rα was up-regulated in CD4 + T cell-mediated allorejection. Data reported that CD4 + T cells and macrophages could directly result in allogeneic graft rejection [10,16,40,41]. Considering that allogeneic grafts have severe inflammatory infiltration, such as CD4 + T cells and macrophages, we postulated that IL-27Rα may act as a targeted biomarker to monitor acute allogeneic graft rejection, based on graft inflammatory cell infiltration, non-invasively and visually.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies with different cellular injury models have shown that hemin can suppress ROS production via enhancing HO-1 expression. 67,68 FIGURE 9. (A) The electrodes of the MEA were classified into three categories according to their distance to the optic nerve head.…”
Section: Discussionmentioning
confidence: 99%